Pembelajaran Bahasa Arab dengan Menggunakan Thariqah al-Qiro’ah: A Systemic Review - Asti Nazhyfa; Wiza Novia Rahmi; Mahyudin Ritonga (Edukasi Lingua Sastra, 2022)
Learning methods have an important position in achieving the set learning goals. Experts have found various methods that can be applied in language learning, one of which is thariqah al-qiro'ah, this paper will reveal how thariqah al-qiro'ah in theoretical reviews as well as practical reviews. Research is carried out in the form of library research, which is looking for various information related to thariqah al-qiro'ah in various sources then analyzing it to be interpreted as research findings, analysis is carried out by comparing the opinions and results of existing research. The research findings are that thariqah al-qiro'ah is an Arabic learning method used to realize learners who have the ability to read. In its application, thariqah al-qiro'ah begins with the provision of new mufradat to students, discusses together the content of the reading text, asks questions to students related to the text and ends with the provision of exercises related to reading. But this method only focuses on reading skills and does not train students' ability to listen, speak and write.